Ixazomib maintenance therapy in newly diagnosed multiple myeloma: An integrated analysis of four phase I/II studies. (8th May 2019) - Dimopoulos, Meletios A.; Laubach, Jacob P.; Echeveste Gutierrez, Maria Asunción; Grzasko, Norbert; Hofmeister, Craig C.; San‐Miguel, Jesus F.; Kumar, Shaji; Labotka, Richard; Lu, Vickie; Berg, Deborah; Byrne, Catriona; Teng, Zhaoyang; et al.
Abstract: Objectives: To evaluate the safety and efficacy of maintenance therapy with the oral proteasome inhibitor ixazomib in patients with newly diagnosed multiple myeloma (NDMM) not undergoing transplantation. Methods: Data were pooled from four NDMM phase I/II studies; patients received induction therapy with once‐ or twice‐weekly ixazomib plus lenalidomide‐dexamethasone (IRd), melphalan‐prednisone (IMP), or cyclophosphamide‐dexamethasone (ICd), followed by single‐agent ixazomib maintenance, given at the last tolerated dose during induction, until disease progression, death, or unacceptable toxicity. Results: A total of 121 patients achieved stable disease or better after induction (weekly IRd, n = 25; twice‐weekly IRd, n = 18; weekly or twice‐weekly IMP, n = 35; weekly ICd, n = 43) and received ≥ 1 dose of ixazomib maintenance. Grade ≥ 3 drug‐related adverse events occurred in 24% of patients during maintenance; each event was reported in ≤2% of patients. Rates of complete response were 22% after induction and 35% after maintenance. A total of 28 patients (23%) improved their response during maintenance. Conclusions: Ixazomib maintenance following ixazomib‐based induction is associated with deepening of responses and a positive safety profile with no cumulative toxicity in patients with NDMM not undergoing transplantation, suggesting that ixazomib is feasible for long‐term administration. Phase III investigation of ixazomib maintenance is ongoing.